Transphyseal reconstruction of the anterior cruciate ligament in prepubescent athletes - Streich, Nikolaus; Barié, Alexander; Gotterbarm, Tobias; Keil, Maximilian Martin; Schmitt, Holger (Knee surgery, sports traumatology, arthroscopy, 2010)
ACL reconstruction in adolescents undergoing or being beyond the final growth spurt can be performed as in adults without major concern of growth disturbance. Whereas for the young athlete with wide-open physis a lot of controversy still exists about the technical aspect of the procedure to minimise the risk of growth disturbance. Between 10/1997 and 10/2002 31 children graded Tanner stage 1 or 2 (median age 11 years) with an intraligamental rupture of the anterior cruciate ligament were enrolled. Seventeen patients with coexisting intraarticular damage (meniscus, osteochondral flake) underwent transphsyeal reconstruction of the ACL with the use of an autogenous semitendinosus tendon graft, whereas 14 patients without coexisting pathologies received a nonoperative regime. Growth disturbance, functional and radiographic outcome could be evaluated in 28 patients at a median of 70 months after initial treatment. No patient had clinical or radiological evidence for varus/valgus malalignment or leg length discrepancy. The mean of subsequent body growth within the study population was 20.3 cm. Patients operated on revealed significant (P < 0.05) better clinical (KT-1000 side-to-side difference, pivot shift) and functional results according to the IKDC (median, 95 vs. 87), Lysholm (median, 93 vs. 84) and the Tegner score. More than half of the conservatively treated patients (58%) had subsequent surgery due to persistent instability. Transphyseal reconstruction of intraligamental ACL ruptures with an autologous ST graft yielded superior clinical results if compared to a nonoperative treatment in immature prepubescent patients being Tanner stage 1 and 2.